A comparative digital morphometric study of lung tissue in saltwater and freshwater drowning. (May 2019) - Barranco, Rosario; Castiglioni, Claudia; Ventura, Francesco; Fracasso, Tony
Highlights: The study investigates whether APE is present in both fresh and saltwater drowning. Alveolar spaces was calculated by means of image analysis software. Mean alveolar area in FWD was significantly higher than in SWD and controls. No statistical differences were observed between saltwater drowning and controls. The results suggest that APE is not a typical sign of death by saltwater drowning. Abstract: Acute pulmonary emphysema (APE) is describedin cases of drowning and can be considered as a sign of vitality. In our experience, however, APE is not very evident in cases of saltwater drowning. The present study aims at investigating whether APE is present in both fresh and saltwater drowning by means of digital morphometric analysis of lung tissue. We investigated and compared a group of saltwater drowning and a group of freshwater drowning, while cases of acute external bleeding were investigated as negative control group. Tissue samples from each pulmonary lobe were collected during autopsy and examined by optical microscope. The area of alveolar spaces was calculated by means of image analysis software, recording the mean alveolar area (MAA) for each group. MAA was 24, 852 μm 2 in the saltwater drowning group, 34, 133 μm 2 in the freshwater drowning group and 21, 871 μm 2 in the negative control group. The MAA in freshwater drowning was significantly higher than in saltwater drowning and controls. No statistical differences were observed between saltwater drowning and controls. The results of this study suggest that APE is not a typical sign of death by saltwater drowning.